Investigation on Science Education Chemistry Students’ Attitudes towards Online Instruction in Public Universities - Joy Anulika Eke; Maxwell Chukwunazo Obikezie; Madeleine Chinyere Nwankwo (Journal of Research in Environmental and Science Education, 2025)
Despite the importance of Chemistry online instruction like accessibility, flexibility, and the quality of learning experiences some students seems not to appreciate it due to some attitude factors like lack of skills. Due to this, the study examined science education Chemistry students’ attitudes towards online instruction in public universities. Four research questions guided the study. The study adopted a descriptive Survey design. The sample size of the study was 195 undergraduate chemistry education students from the population of 312 comprising of 217 males and 95 females in Anambra State public universities. The study adopted a random sampling technique and data were collected through structured questionnaire administered to the students from Nnamdi Azikiwe University, Awka and Chukwuemeka Odumegwu Ojukwu University, Uli. The questionnaire which was adapted from Azeta and Durowoju (2018) titled Chemistry Education Students’ Attitudes Towards Online Instructions (CESATOI) was validated by three experts in the Department of Science Education, faculty of education, Nnamdi Azikiwe University and its reliability coefficient of 0.86 was established using Cronbach alpha. The data collected were analyzed using mean. Findings revealed that students generally have a positive attitude towards online instruction of computer science as a course. While these attitudes exist among students, the findings also indicated some challenges that undermine the quality of online instruction and the strategies to enhance the system. Based on the findings, it was recommended that Undergraduate chemistry education students should avail themselves to participate fully in the different possible strategies as identified by putting more interest in the use of online instruction. This will help to validate the level of challenges that has been dealt with. To enhance the quality of online instruction, and to foster right attitude among students, the institutions and government should provide a conducive online learning environment, free network access and good technological support. From the recommendations it was concluded that chemistry education students display a positive attitudes towards online instruction.